Investigating the behavior of the prequalified ConXL connection strengthened with T-stub - Ghamari, Ali; Tavakoli, Sajad; Putra Jaya, Ramadhansyah; Thongchom, Chanachai (Institution of Structural Engineers, 2025)
While the box-columns section provides significant advantages, including a low slenderness ratio that enhances buckling strength, high post-buckling strength, and excellent ductility, the implementation of continuous plates for moment-resisting frames presents a range of challenges. As a result, numerous solutions have been proposed to tackle these issues effectively. Among these, the ConXL connection has emerged as a particularly promising option, demonstrating superior performance and gaining widespread acceptance in the engineering community. This paper focuses on the ConXL connection, conducting a thorough examination of its properties and exploring innovative methods to enhance its performance through both numerical and parametric studies. Specifically, five distinct model types were analyzed: ConXL with Reduced Beam Section (RBS), ConXL without RBS, ConXL with T-stub, ConXL with T-stub and Concrete-Filled Tubular (CFT) columns, and web-connected models. The findings revealed that all variations of the ConXL configurations exhibited satisfactory performance, achieving a rotation capacity that exceeded 0.04 radians. In these instances, the capacity of the connections was shown to surpass 80 % of the plastic moment of the beam. Moreover, the integration of a T-stub significantly improved energy dissipation and ultimate strength within the connection. It was observed that substituting a conventional beam for an RBS increased stress levels in the panel zone and connections. However, optimal performance was attained by incorporating T-stubs into the designed columns, and it was noted that an unfilled column could be effectively utilized, provided that the thickness of the column is appropriately increased.